A Critical Review of the Role of Thin Liquid Films for Modified Salinity Brine Recovery Processes. (December 2020) - Guo, Haoli; Nazari, Negar; Esmaeilzadeh, Soheil; Kovscek, Anthony R.
Abstract: Low salinity water injection (LSWI) is the process of injecting modified salinity brine with controlled ionic composition to achieve increased oil recovery compared to conventional waterflooding. This paper reviews the most recent advances in proposed low salinity mechanisms, but specifically emphasizes the role of thin liquid films in crude oil/brine/rock systems. Importantly, thin water films on rock surfaces affect hydraulic resistance of pore channels as well as phase-trapping mechanisms. As films become thicker, they provide greater lubrication of oil droplets and hence, flow resistance decreases. Consequently, films dictate oil and water distribution in porous media and determine the wettability of crude oil/brine/rock systems under static and dynamic conditions. The stability of the thin water films depends on the interactions between the oil/brine and the calcite/brine interfaces through van der Waals, electrostatic, and structural forces. Graphical abstract: Image 1